The forgotten key players in rheumatoid arthritis: IL-8 and IL-17 – Unmet needs and therapeutic perspectives - Elisa Gremese; Elisa Gremese; Elisa Gremese; Barbara Tolusso; Barbara Tolusso; Dario Bruno; Dario Bruno; Simone Perniola; Gianfranco Ferraccioli; Stefano Alivernini; Stefano Alivernini; Stefano Alivernini (Frontiers in Medicine, 2023)
Despite the relevant advances in our understanding of the pathogenetic mechanisms regulating inflammation in rheumatoid arthritis (RA) and the development of effective therapeutics, to date, there is still a proportion of patients with RA who do not respond to treatment and end up progressing toward the development of joint damage, extra-articular complications, and disability. This is mainly due to the inter-individual heterogeneity of the molecular and cellular taxonomy of the synovial membrane, which represents the target tissue of RA inflammation. Tumor necrosis factor alpha (TNFα) and interleukin-6 (IL-6) are crucial key players in RA pathogenesis fueling the inflammatory cascade, as supported by experimental evidence derived from in vivo animal models and the effectiveness of biologic-Disease Modifying Anti-Rheumatic Drugs (b-DMARDs) in patients with RA. However, additional inflammatory soluble mediators such as IL-8 and IL-17 exert their pathogenetic actions promoting the detrimental activation of immune and stromal cells in RA synovial membrane, tendons, and extra-articular sites, as well as blood vessels and lungs, causing extra-articular complications, which might be excluded by the action of anti-TNFα and anti-IL6R targeted therapies. In this narrative review, we will discuss the role of IL-8 and IL-17 in promoting inflammation in multiple biological compartments (i.e., synovial membrane, blood vessels, and lung, respectively) in animal models of arthritis and patients with RA and how their selective targeting could improve the management of treatment resistance in patients.